(untitled) (Research, Society and Development, 2022)
The aim of the study was to evaluate the effects of cardiorespiratory rehabilitation (CR) alone and associated with transcranial photobiomodulation (PBMt) on distance walked (WD), pulmonary function and quality of life in individuals with spasticity. Participants were divided into two groups: Transcranial photobiomodulation group (PBMtG, CR + active PBMt, n=8) and placebo group (PG, CR + sham PBMt, n=7). The CR consisted of 12 weeks of treatment, 2x week for 1 hour, including aerobic, respiratory and resistance exercises of the lower limbs. For PBMt, the laser cluster was used (λ= 680 nm and 3 lasers at λ= 808 nm, total energy of 36 J/point) at points F7, F8, AFz. WD, spirometry, manovacuometry and SF-36 were evaluated at baseline and reassessment at 8 and 12 weeks. The WD increased by 165.43 meters and 222.46m at 12 weeks for PBMtG and PG, respectively, with intragroup statistical differences (p<0.05) and no intergroup difference (p>0.05). An increase in the peak expiratory flow index was observed only in the FG in the baseline analysis x12 weeks (p<0.05). The PBMtG showed an increase in MIP and MEP by 20% (8 weeks) and 15% (12 weeks). In the SF-36, the difference in relation to the baseline, the physical aspects and pain domains were verified for the growth behavior PBMtG, and for the decrease PG. It was concluded that the WD improved in the PBMtG and PG after the intervention, without a potentiating effect on the performance in the PBMtG and that PBMt seems to have influenced the respiratory mechanics of the PBMtG and the physical aspects and pain of the SF-36.